(untitled) (World Journal of Current Medical and Pharmaceutical Research, 2019)
Alkaloids are a category of molecules in nature around the globe with a relatively large occurrence. These are chemicals and biomolecules that are very complex. Alkaloids are compounds of a very diverse class of secondary plant metabolites; alkaloids, such as anticholinergics, antitumor, diuretic, antiviral, antihypertensive, antiulcer, analgesic, and anti-inflammatory, have been linked to the extensive list of biological activities. The basic character of alkaloids allows salts to be formed with mineral acids or organic acids, alkaloid salts are usually soluble in water and dilute alcohols, and are not soluble in organic solvents except in rare cases. This research is carried out mainly in the context and classification of alkaloids and alkaloids pharmacological practices.